Association of host transcriptomic and microbiome profiles with food allergy - Lee, Khui Hung (Curtin University, 2021)
This thesis explores the molecular mechanism of food allergy among children in Perth, Australia. The overall aim of this thesis is to systematically elucidate the association of gene expression and microbiome with the pathogenesis of food allergy. The results of this thesis contribute towards a greater understanding of mechanisms underlying food allergy and may have utility in providing targets or biomarkers for better prediction and early identification of food allergy.